A bibliometric analysis with data OpenAlex and mining methods of 41 525 abstracts of papers on the health impact of air pollution published between 1960 and 2022 - Bogdan Bochenek; Mateusz Jankowski; Joanna Wieczorek; Marta Gruszczyńska; Jarosław Pinkas; Mariusz Figurski (International Journal of Occupational Medicine and Environmental Health)
Exposure to air pollution is a significant risk factor for non-communicable diseases. This bibliometric analysis with data mining methods aimed to identify the most common air pollutants and health effects mentioned in research on the health effects of air pollution published in 1960–2022. The OpenAlex database and OpenAlexR package were used to retrieve abstracts of scientific papers on the health impact of air pollution published in 1960–2022. Publication year, type of air pollutant, type of diseases analyzed in the study, and affiliation of the authors were analyzed using data mining methods. Out of 41 525 papers published in 1960–2022, 22.3% (N = 9255) listed particulate matter 2.5 (PM 2.5 ) in the abstract at least once, 13.2% (N = 55 011) listed PM 10 , 11.6% listed carbon monoxide (CO) (N = 4829), 11.5% (N = 4784) listed nitrogen dioxide (NO 2 ), 7.5% listed sulfur dioxide (SO 2 ) (N = 3106), and 7.1% of papers listed ozone (O 3 ) (N = 2943). Respiratory diseases were the most common health effects. Most of the papers (N = 1880) were focused on PM 2.5 . The most common co-occurrence patterns included the impact of PM 2.5 on lung, heart, and asthma. In total, in 1960–2022 authors from 165 different countries published at least 1 paper on the health effects of air pollution. This study provided bibliometric data on the number and topics of papers on the health impact of air pollution published in the past 60 years. Most of the papers were published by authors from the global North with a very limited number of papers on air pollution and health published by the authors from Africa and South America. Int J Occup Med Environ Health. 2025;38(3):222–235